The crystal structure of 1,1′-(phenazine-5,10-diyl)bis(heptan-1-one), C26H34N2O2 - Tang Wenhao; Li Weihuan (Zeitschrift für Kristallographie - New Crystal Structures, 2025)
C26H34N2O2, monoclinic, P21/c (no. 14), a = 12.3394(3) Å, b = 13.3376(3) Å, c = 17.5735(4) Å, β = 123.246(1)°, V = 2418.83(10) Å3, Z = 4, R gt(F) = 0.0538, wR ref(F 2) = 0.1594, T = 298 K.